Approach to a simplified numerical optimization of low-power Hall thrusters. (June 2018) - Wang, Y.M.; Xu, S.; Levchenko, I.; Huang, S.Y.; Xu, L.X.; Yu, M.Y.
Abstract: Simple, efficient, multi-parametrical design-oriented approach to optimize key parameters of miniaturized, low-power Hall-type thrusters potentially suitable for application at Cubesats and other compact spacecraft is proposed, designed, applied to a typical thruster design, and tested experimentally. Based on the detailed calculations of magnetic field, temperature distribution, electron and ion energies and other vital parameters in the detailed design with specific materials, the key power fluxes and critical temperature points in the thruster could be determined. The obtained results were then compared with the available test data, and the model was verified. The paper thus proposes an architecture of the modular CAD-based approach for the fast assessment of the Hall thruster performance at the design and test stages, and could be useful to design and optimize low-thrust devices vitally required for propelling small satellites and space vehicles of various types, including Cubesats, micro-satellites and interplanetary space probes. Highlights: Simple design-oriented approach to optimize key parameters of miniaturized, low-power Hall-type thrusters is proposed. Based on the detailed calculations, the key power fluxes could be determined. The obtained results were compared with the available test data, and the model was verified.